Méthodes d’évaluation de la qualité hygiénique et microbiologique du lait cru de vache - BELHANDOUZ, Mohamed El Bachir (My University, 2020)
A study on methods for assessing the hygienic and microbiological quality of raw cow's milk is being carried out. The work of some authors is presented and discussed. The result of the physico-chemical analyzes show certain variability between the samples of crude taken milk. This is the case of the pH which varies with an average value of 6,57, an acidity of 16 ° D, an average M.G content of 35g / L. All of these values generally comply with the standards admitted to the J.O.R.A. However, the average density value (1023g / L), the average rate is slightly below the 7,87% standard. Microbiological analyzes revealed a load of around 0,08.105 UFC / ml for FTAM, more less the standard setting the threshold at 105 UFC / ml. In addition, a high load of Totals coliforms and Fecals Coliforms was recorded which exceeds the standard set at 103 UFC/ml, that reflects contamination of fecal origin. A total absence of pathogenic germs (S. aureus, salmonella, Clostridium sulfito-reducteur) was noted.
Keywords: raw milk; cow; quality; physico-chemic; microbiology